PENGEMBANGAN PERANGKAT PERCOBAAN KONSEP ROTASI UNTUK PEMBELAJARAN FISIKA DI SMA DAN UNIVERSITAS - Hendar Sudrajad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This research aim to develop the attempt peripheral conception the effective giration for the study of middlephysics at school and university. Research approach used by research and development method (R&D).Product from this research is consisted of by two component, namely rotation table and operation guidance.Effectivity of peripheral experiment developed in this research is evaluated from two aspect, namely validityand practicality. Indicator for the examination of validity is contains validity, empirical validity andconstruct validity. For practicality test, the component of evaluations is empirical practicality and studentopinion in a test-drive limited by entangling student of SMA.Technique analyse the data used in this researchis descriptive analysis. Pursuant to gathering result and analyse the data, obtained by picture that attemptperipheral developed in this research own the very high effectiveness to nine of attempt items and higheffectiveness to three attempt items. Thereby, attempt peripheral developed in this research can be expressedcompetent to be used in high school and university, especially to nine attempt item identified.